Limnoperna fortunei (Dunker, 1857) larvae : from abiotic filters to potencial impacts on phytoplankton community. - Silva, Jéssica Ernandes da (2021)
The success of biological invasions depends on overcoming environmental filters. After the filters are transposed and subsequently established, invasive species can reach high densities and cause impacts, such as loss of biodiversity and damage to the functioning of ecosystems. The golden mussel (Limnoperna fortunei) is an invasive bivalve in South America and presents high densities in invaded environments. It has a planktonic larval stage, divided into five stages, and an encrusting adult. The larval stage is considered the main propagule of the species. It is known that abiotic factors act differently on larval stages, as these present morphological and physiological differences. Some works shown the ability of L. fortunei to select groups and functional traits of phytoplankton species, but these studies are experimental and with adult representatives. Considering that larvae are the main propagule of the species, therefore, abiotic filters act primarily on them, we sought to (i) evaluate the population structure of L. fortunei larvae and its relationship with environmental factors in lotic environments in the floodplain of the Upper Paraná River. In addition, considering that larvae can reach high density values, we also sought to (ii) identify the potential impacts of high larval densities on the taxonomic and functional diversity of phytoplankton, and their effects on ecosystem functioning. The results showed differences in the age pyramid between the evaluated environments, and found that most environmental filters act on the early larval stages. Among these filters, turbidity stands out. We also identified a negative effect of L. fortunei larval density on the functional and taxonomic diversity of the phytoplankton community. The effects of larval density on these facets of phytoplankton diversity resulted in indirect negative effects on the biomass stock of the community of these producers. It's expected that knowledge about the filters that control larval densities of L. fortunei can contribute to the control and management of the species, in order to avoid major impacts on the phytoplankton, and consequently, on the environment.